1997
DOI: 10.1126/science.275.5304.1281
|View full text |Cite
|
Sign up to set email alerts
|

Diring Yuriakh: A Lower Paleolithic Site in Central Siberia

Abstract: Lower Paleolithic artifacts have been recovered from a single occupation surface within stratified deposits at Diring Yuriakh, an archaeological site in central Siberia. Thermoluminescence age estimates from eolian sediments indicate that the cultural horizon is greater than 260,000 years old. Diring Yuriakh is an order of magnitude older than documented Paleolithic sites in Siberia and is important for understanding the timing of human expansion into the far north, early adaptations to cold climates, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 9 publications
0
44
0
1
Order By: Relevance
“…Siberia has been inhabited by hominins for hundreds of thousands of years, with some of the known archeological sites being older than 260,000 yr (Waters et al 1997). Neanderthals inhabited Europe and Siberia until ∼40,000 yr ago (40 kya) (Hublin 2009), and anatomically modern humans expanded to these regions 60-40 kya (Hublin 2012).…”
mentioning
confidence: 99%
“…Siberia has been inhabited by hominins for hundreds of thousands of years, with some of the known archeological sites being older than 260,000 yr (Waters et al 1997). Neanderthals inhabited Europe and Siberia until ∼40,000 yr ago (40 kya) (Hublin 2009), and anatomically modern humans expanded to these regions 60-40 kya (Hublin 2012).…”
mentioning
confidence: 99%
“…In the upper excavations, the stratigraphic range of both units is very likely to be much wider than in the lower excavations. This hypothesis is supported by the results of TL dating of sediments by Waters et al (1997). However, the stratigraphic position of the cultural layer in the upper excavations remains unclear.…”
Section: Problems With the General Stratigraphy At Diringmentioning
confidence: 51%
“…Other site investigators (Mochanov, 1992(Mochanov, , 1993Waters et al, 1997) have suggested that a single, continuous cultural stratum extended from the lower section towards the east, where it is overlain by Middle and Late Pleistocene deposits (Figures 3 and 4) (layers 6 -13 in Mochanov [1992Mochanov [ , 1993; units IIIa -IIIe in Waters et al [1997]). …”
Section: Problems With the General Stratigraphy At Diringmentioning
confidence: 97%
See 2 more Smart Citations